The Awakening of Pisco in Chile [el Amanecer del Pisco en Chile] - Lacoste, P; Soto-González, N (Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal, 2014)
This paper analyzes the historical antecedents of pisco (grape brandy) in Chile from unpublished original documents of the Archivo Nacional (National Archives) from the end of the 17th century to the beginning of the 18th century. This work also shows that during Spanish domination in the 17th century, the tradition of making brandy from grape wine using stills was consolidated in the northern Kingdom of Chile. In addition, a flow of brandy exports from the very early 18th century is demonstrated.